The Effect of Audit Switching, Financial Distress and Audit Firm Reputation on Audit Delay: A Study on Manufacturing Companies Listed on Indonesia Stock Exchange - Ayu Rahmawati; Yulinartati -; Riyanto Setiawan Suharsono (Universitas Padjadjaran, 2023)
This study investigates the impact of audit switching, financial distress and audit firm reputation on audit delay in manufacturing sector companies listed on the Indonesia Stock Exchange between 2017 and 2021. Purposive sampling was employed with a sample size of 23 manufacturing businesses, this study relied on secondary data from firm financial reports. Multiple linear regression was employed as the analytical model in this investigation. According to the test result, audit switching and financial distress have a considerable impact, although audit firms’ reputation has no effect on the incidence of audit delay.